2018
DOI: 10.1021/acsami.8b10426
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as a Novel Nanocarrier System for Doxorubicin Delivery to MDR Cancer Cells: In Vitro and In Vivo Evaluation

Abstract: Curcumin (CRC) has been widely used as a therapeutic agent for various drug delivery applications. In this work, we focused on the applicability of CRC as a nanodrug delivery agent for doxorubicin hydrochloride (DOX) (commercially known as Adriamycin) coated with poly(ethylene glycol) (PEG) as an effective therapeutic strategy against multidrug-resistant cancer cells. The developed PEG-coated CRC/DOX nanoparticles (NPs) (PEG-CRC/DOX NPs) were well localized within the resistant cancer cells inducing apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…As aforementioned, co-administration of procyanidin, scillarenin, polmoric acid, betulinic acid, and a high dose of QUE could enhance the efficacy of anticancer agents against brain cancer by inhibiting efflux transporters in the BBB. A recent study reported that curcumin nanoparticles loaded with DOX could more efficiently deliver and localize DOX into P-gp-and MRP-overexpressed cancer cells (e.g., glioblastoma) by inhibiting those efflux transporters, thereby enhancing the anticancer efficacy in the tumor-xenograft model compared to the treatment of DOX solution, while this synergistic effect is the most remarkably exhibited in the treatment of polyethylene glycol-conjugated curcumin nanoparticles loaded with DOX [103].…”
Section: Combinatorial Therapies Of Natural Compound and Drug For Synmentioning
confidence: 99%
“…As aforementioned, co-administration of procyanidin, scillarenin, polmoric acid, betulinic acid, and a high dose of QUE could enhance the efficacy of anticancer agents against brain cancer by inhibiting efflux transporters in the BBB. A recent study reported that curcumin nanoparticles loaded with DOX could more efficiently deliver and localize DOX into P-gp-and MRP-overexpressed cancer cells (e.g., glioblastoma) by inhibiting those efflux transporters, thereby enhancing the anticancer efficacy in the tumor-xenograft model compared to the treatment of DOX solution, while this synergistic effect is the most remarkably exhibited in the treatment of polyethylene glycol-conjugated curcumin nanoparticles loaded with DOX [103].…”
Section: Combinatorial Therapies Of Natural Compound and Drug For Synmentioning
confidence: 99%
“…However, the average diameter of PEG-b-PAsp-g-PBE/DOX was determined as 95 nm by TEM ( Figure 4) and DLS ( Figure S7), which increase with the effect of the dox encapsulation. Their, surface charges vary from À23.9 mV to À16.1 mV, demonstrating that DOX has been loaded through the electrostatic interaction (Rejinold et al, 2018).…”
Section: Preparation Of Polymeric Micelles and Drug Release In Vitromentioning
confidence: 99%
“…One of the advantages of using nanocarriers to codeliver chemotherapy drugs and active constituents of plants is their capability to reverse MDR [32,91,148](seen Figure 2). Rejinold et al [88] investigated using CUR as the nanocarrier to load PEG-doxorubicin hydrochloride for HCT-8/DOX-resistant cells to increase the in vivo and in vitro antitumor efficacy. In vitro anti-MDR experiments have shown that PEG CRC/DOX NPs had a higher antimetastatic and antiproliferative effect on MDR cancer cells while normal fibroblasts were unaffected.…”
Section: Multidrugmentioning
confidence: 99%